A new method for endovascular implantation of endocardial electrode - O.K. Zenin; O.S. Antonyuk; A.S. Kuznetsov; A.N. Mitroshin; N.A. Kuznetsov; A.V. Dmitriev (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2021)
Background. Creating a new affordable and easy to use in medical practice, highly effective and reliable method of endovascular implantation of the endocardial electrode is an urgent task. The purpose of this work id to introduce a new method of endovascular endocardial electrode implantation. Results. The method of endovascular endocardial electrode implantation is described in detail, characterized in that, firstly, to clarify the nature of individual anatomical features, contrast radiography of a potentially suitable vessel is performed before the procedure; secondly, if available, instead of the J-conductor, a PT2-type coronal conductor is used for the endocardial electrode. Conclusions. The described method allows shortening the time of the endocardial electrode, reducing the size of the surgical field and thereby reducing the risk of septic complications, which makes the operation less dangerous and more effective.